Dinamika Risk Dan Return Investasi Saham Jakarta Islamic Indeks (JII) Di Masa Pandemi Covid 19 - Muhammad Sultan Mubarok (Universitas Serang Raya, 2022)
The purpose of this study is to analyze the dynamics of returns and risks of Sharia stock investment in JII during the Covid-19 pandemic period. This type of research is quantitative using an observational descriptive research design. This research was conducted in January 2019 – December 2021. The sampling technique uses purposive sampling, from 30 populations that meet the sample criteria of 16 companies. The results of this study concluded that JII's risk and stock returns for 2019-2021 experienced dynamic fluctuations. In 2019-2021, stock returns can be said to be unstable or even tend to decline, this is evidenced by the trendline that is pointing downwards, while for risks in the pandemic year, fluctuations tend to be more stable than returns.